The Effect of Financial Planning, Sustainable Investment, and Risk Management on Business Sustainability in the SME Sector - Aspiati A. Samiun; Eko Sudarmanto; Thitus Gilaa; Jamaluddin Majid; Purwanto Purwanto (Sciences du Nord Economics and Business, 2024)
This study examines the effect of financial planning, sustainable investment, and risk management on business sustainability within the SME sector. A quantitative approach was employed, utilizing a sample of 80 SMEs and data collected through structured questionnaires. The responses were measured using a 5-point Likert scale, and the data were analyzed using SPSS version 25. The results indicate that financial planning, sustainable investment, and risk management all have a significant positive impact on business sustainability. The findings suggest that SMEs that adopt comprehensive financial planning, integrate ESG factors into their investment decisions, and implement robust risk management strategies are better positioned to achieve long-term sustainability. This research provides practical insights for SME owners, managers, and policymakers to enhance resilience and ensure business growth in a competitive environment.